Aktivitas Antifungi Ekstrak Etanol dan Metanol Batang Pisang Mauli 100% - Maharani Laillyza Apriasari (Fakultas Kedokteran Gigi Universitas Jember, 2015)
Background: North Hulu Sungai Banjarmasin people are using banana stem mauli to accelerate wound healing in the skin. Mauli banana stem extract contains antimicrobial and antioxidant effects. Need the development of traditional plants that can be used as a topical antiseptic drug in the oral cavity. Purpose: to determine the anti fungal affectivity of methanolextract of 100% mauli banana stem compared with the ethanol extract of 100% mauli banana stem. Methods and materials: pure laboratory experimental research with the completely randomized design using 3 treatments with 9 replications. Making 100% banana mauli stem extract by maceration method using the solution of ethanol and methanol. The sample was a pure culture of Candida albicans. Saboroud agar petridish were contained Candida albicans that have given filter paper soaked for 3 hours with100% methanol extract of mauli banana stem, 100% ethanol extract of mauli banana stem, and 0,2% Clorhexidine gluconate. Inhibition zone diameter of three treatments was compared after doing incubation for 1 day. It using the diffusion method. Results: Kruskal Wallis test of the three treatment resulted p value=0.00(p <0.05) that H0 was rejected, so it could be concluded that there were significant differences between the three treatments. Mann Whitney test resulted that the treatment of 100% ethanol was compared with100% methanol resulted p = 0.00 (p <0.05).There was a significant difference between the treatment of 100% ethanol and 100% methanol to the growthness of Candida albicans. Conclusion: The results of the study it appears that the banana stem mauli have antimicrobial activity. Methanol extract of banana stem mauli has a total flavonoids was higher than the ethanol extract of banana stem mauli. This makes methanol extracts had higher antifungal activity than the ethanol extract.